Denai Kapur: Repurpose. Rejuvenant. Restore. - Muhammad Hazimi bin Azman (Trends in Undergraduate Research, 2023)
The Denai Kapur was designed as a townhall that serves as difference spaces based on different occasions. Located near to the Dewan Suarah and Sekolah Jenis Kebangsaan Chung Hua, the Denai Kapur is expected to be used not only by the students, but also will be beneficial towards the local people around the area. The layour of the Denai Kapur was planned based on the site given, to be able to adapt to the site constraints. Being that the existing limestone was the most important element within the site, most of it remained untouched as the building was designed surrounding it.